MEMBANGUN IMAJINASI DAN FANTASI MELALUI BUKU- BUKU CERITA BERGAMBAR UNTUK ANAK-ANAK - Widyastuti Purbani (Imaji, 2007)
In what so-called the era of image and imagination, the words imagination and fantasy commonly receive negative connotation, and are usually misunderstood as destructive rather than productive, even among intellectuals and educators. This paper aims at giving clarification on the importance and contribution of imagination and fantasy in education and transformation of knowledge. Illustrations on how to stimulate young people's imagination and fantasy using picture books, and what kind of picture books have the ability to stimulate imagination and fantasy will be revealed at the later part of this writing.